Qualitative Study Examining the Effects of the COVID-19 Pandemic on the Homelessness Community Using PhotoVoice: Methodology and Lessons Learned - Fiona M. Asigbee; Landon Ranck; Anna S. Pruitt; Rachyl L. Pines; Cara Silva; Luke Barrett; Julia K. Petras; Monica Ray (International Journal of Qualitative Methods)
Photovoice (PV), a Community-based Participatory Research (CBPR) method, has been used to better understand the lived experience of homelessness. As part of PV, participants use photography to capture phenomena of importance, engage in critical dialogue and analysis, and communicate findings to policymakers and the community. This paper examines: (1) the methodology for recruiting individuals experiencing homelessness (IEH), (2) innovative and emerging applications of PV for capturing lived experiences during a pandemic, (3) strategies for designing partnerships between multi-sectional organizations, (4) the application of infection prevention and control protocols, (5) the use of robust, collaborative data analysis methods, (6) approaches for disseminating and implementing key findings, and (7) lessons learned. Conducting a PV study with IEH can present challenges and as a result, such studies often have small sample sizes (6-13 people). This study was able to recruit and engage 38 participants across multiple sub-populations of IEH during a global pandemic. Partnerships between a healthcare organization, community organization focused on addressing local homelessness, shelter and service agency staff, community members interested in assisting with the study, and a software development company were integral to the success of the project. Participants provided input on how they would like the study findings shared with the public and were invited to join planning meetings for public presentations. Future PV studies conducted among populations experiencing homelessness should consider strategic involvement of partners at various levels (service providers, community members, and participants).